EFFECT OF THE TOURIST GUARD PROGRAM ON THE INCIDENCE OF OBSTETRIC COMPLICATIONS AT TALANGO COMMUNITY HEALTH CENTER - Kurniyati, Eka Meiri; Sri Yunita Suraida Salat; Yulia Wardita; Huzaimah, Naily; Hidayati, Khafifa (Poltekkes Kemenkes Tasikmalaya, 2025)
One of the benchmarks for the success of a country's development is improving the quality of life, which is one of the main prerequisites in developing human resources (HR). One of the causes of the high maternal mortality rate is because the mother experiences obstetric complications. Complications of pregnancy, childbirth and postpartum are conditions that cause health problems in pregnant women, mothers giving birth, mothers in the postpartum period, or fetuses in the womb. This condition can occur directly or indirectly, including due to infectious or non-infectious diseases that have the potential to endanger the lives of the mother and fetus. Talango Health Center itself has a tourist post. The Tourist Post (integrated movement to reduce maternal and neonatal mortality) is a new innovation carried out by the Talango Health Center. This innovation is carried out by village representative cadres in Talango sub-district, each village appoints 2 cadres as representative cadres, the 2 cadres will become coordinators for the cadres in their village. Each cadre monitors high-risk pregnant women, babies and postpartum mothers to ensure that the condition of the mother and baby can reduce the risk of maternal and neonatal mortality. The purpose of this study was to determine the effect of the tourist guard program on the incidence of obstetric complications. This type of research is an observational analytical study with a cross-sectional design . The independent variables in the study include the tourist guard program which includes assistance for pregnant women, pregnancy classes, postpartum visits and transportation. While the dependent variable in this study is the incidence of obstetric complications. The population in this study were all fertile couples in the Talango Health Center work area totaling 6910 people. The sample size used a cross-sectional sample size of 73 people with a simple random sampling technique. The bivariate analysis in this study used a simple regression test. The results of the simple regression test between assistance for pregnant women, pregnancy classes and postpartum visits with the incidence of obstetric complications had a significant effect. While for the results of the data analysis of pregnant women who received pick-up and drop-off services, there was no effect between receiving pick-up and drop-off services for pregnant women to do ANC with the incidence of obstetric complications. The conclusion of this study is that there is an effect of the tourist guard program on the incidence of obstetric complications